Axillary lymph node metastases from unknown primary: A French multicentre study. (April 2018) - Ouldamer, Lobna.; Cayrol, Marie; Vital, Mathilde; Fièvre, Claire; Druelles, Marion; Arbion, Flavie; Body, Gilles; Lévêque, Jean; Fritel, Xavier
Abstract: Purpose: The aim of the study was to investigate the management and prognosis of axillary cancers from unknown primaries (CUPax). Methods: We included all patients with lesions described as axillary nodal metastases from an unknown primary referred to four French tertiary breast cancer centres between January 1988 and December 2012. The inclusion criteria comprised: no sign of primary breast cancer on clinical examination nor on imaging (mammography, ultrasonography and breast MRI) and no primary tumour identified elsewhere. Results: CUPax represented 1.8% of all metastatic axillary lymphadenopathies in our institutions. The overall survival rate was 71%, and 16.7% of patients had secondary inflammatory breast cancer signalling a posteriori that CUPax originated from the breast. Factors that favourably affected survival according to univariate analysis were: histological type of non specific adenocarcinoma (versus other types, p = 0.02), only one lymph node involved (versus several, p = 0.04), a normal CA153 serum-level (p = 0.02), no distant metastasis at initial assessment (p = 0.02), no secondary distant metastasis (p = 0.005) and radiotherapy to the ipsilateral breast/chest wall/lymph nodes (p = 0.04). On multivariate analysis including these factors, a histological type of non-specific adenocarcinoma (p = 0.03) and distant metastases (p = 0.03) were identified as independent factors affecting survival. Conclusion: We believe that these results will shed light on current investigations and treatment of this rare entity.